Planning for a sustainable Oslo: the challenge of turning urban theory into practice. Issue 5 (4th May 2017) - Andersen, Bengt; Skrede, Joar
ABSTRACT: Many cities today face challenges related to urban growth. This is also the case in Oslo, currently one of the fastest growing capitals in Europe. In order to prepare for the population growth, a new municipal master plan has been prepared. In this, sustainable development is a prominent concept, and the urban district is going to be densified as part of the strategy. This paper examines some obstacles of turning planning theory into practice. There is a lack of coherence between municipal goals and the actual outcome. The analysis indicates that the official strategy is not able to cater for social sustainability partly due to institutional constraints. Moreover, there is no concise understanding of what sustainability means, which in turn hampers the ability to operationalise the concept in urban planning.